2017
DOI: 10.3389/fphar.2017.00095
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide Reduces Neuropsychiatric Behaviors by Restoring Cortical Electrophysiological Activity in a Mouse Model of Mild Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) represents a major public health problem, which is associated with neurological dysfunction. In severe or moderate cases of TBI, in addition to its high mortality rate, subjects may encounter diverse behavioral dysfunctions. Previous reports suggest that an association between TBI and chronic pain syndromes tends to be more common in patients with mild forms of brain injury. Despite causing minimal brain damage, mild TBI (mTBI) often leads to persistent psychologically debilitating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 52 publications
4
55
1
Order By: Relevance
“…Evaluation of behavioral outcome at 3-6 months might provide additional value using this model. In order to identify the interdependency of vulnerable neurons and malfunction, the cell types/subpopulations of those degenerated neurons ( Zeisel et al, 2015 ) and more analyses of long-term behavioral changes ( Guida et al, 2017 ; Milman et al, 2005 ), including nociceptive response, depression-like activity and sociability, are worthy of further investigation. The serum and/or CSF concentrations of neuron-specific enolase (NSE; ENO2), S100B, myelin-basic protein (MBP), interleukin 6 (IL-6), vascular cell adhesion protein (VCAM1), and cortisol levels ( Berger et al, 2005 , 2006 , 2002 , 2009 ; Heather et al, 2012 ) were detected in children with AHT.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of behavioral outcome at 3-6 months might provide additional value using this model. In order to identify the interdependency of vulnerable neurons and malfunction, the cell types/subpopulations of those degenerated neurons ( Zeisel et al, 2015 ) and more analyses of long-term behavioral changes ( Guida et al, 2017 ; Milman et al, 2005 ), including nociceptive response, depression-like activity and sociability, are worthy of further investigation. The serum and/or CSF concentrations of neuron-specific enolase (NSE; ENO2), S100B, myelin-basic protein (MBP), interleukin 6 (IL-6), vascular cell adhesion protein (VCAM1), and cortisol levels ( Berger et al, 2005 , 2006 , 2002 , 2009 ; Heather et al, 2012 ) were detected in children with AHT.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitoylethanolamide (PEA) is an endogenous lipid compound derived from the reaction between ethanolamine and palmitic acid (Guida et al, 2017a ). PEA is member of the N-acylethanolamides (NAEs) family, characterized for inhibiting mechanisms of secondary injury (Ahmad et al, 2012a ).…”
Section: Introductionmentioning
confidence: 99%
“…PEA is member of the N-acylethanolamides (NAEs) family, characterized for inhibiting mechanisms of secondary injury (Ahmad et al, 2012a ). This pro-homeostatic mediator (Petrosino et al, 2010 ; Petrosino and Di Marzo, 2017 ) exerted neuroprotective effects when administered exogenously in models of brain injury and neurodegeneration (Herrera et al, 2016 ), including spinal cord injury (Genovese et al, 2008 ; Esposito et al, 2011 ), traumatic brain injury (Ahmad et al, 2012a ; Guida et al, 2017a ), stroke (Ahmad et al, 2012b ), Alzheimer's Disease (D'Agostino et al, 2012 ; Scuderi et al, 2014 ), and Parkinson's Disease (Esposito et al, 2012 ). These effects are apparently mediated by the nuclear Peroxisome Proliferator-Activated Receptor (PPAR)-α (Lo Verme et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our behavioral experiments were carried a day after the exposure to pilocarpine and two days after mTBI induction. Previous reports indicated that mTBI mice develop long term neuropsychiatric condition of increased anxiety and later depression (Guida et al, 2017;Belardo et al, 2019). In this sense, could a bigger time lag from the seizures restore the hippocampal abilities of the mTBI treated animals?…”
Section: Discussionmentioning
confidence: 98%